THE POLITICAL USE OF ISLAMIC VARIATION IN INDONESIAN ISLAMIC HIGHER EDUCATION - Ronald A. Lukens-Bull (Jurnal Pendidikan Islam, 2016)
The Indonesian State Islamic Higher Education (PTAIN) system was created to encourage a progressive form of Islam to oppose political Islam and to be apolitical. Because PTAIN are the official government form of Islamic higher education, PTAIN faculty members can be important opinion makers in the Indonesian Islamic community. PTAIN are critical to understanding the Indonesian Islamic community because they engage in innovative scholarship on Islamic theology, ethics, law, and practice and in the education of young Muslim leaders in many fields. This article explores some of the ways PTAIN have been politicized to play a role in the debates about the future of Indonesian Islam which is developing (or at least showing) more complex variations.  It offers a theoretical model for understanding the variation found in Islam.